Preplet stanovanjskih politik in odzivi ljudi na stanovanjske probleme v postsocialističnih mestih - Tsenkova, Sasha (Urbani izziv, 2014)
This article explores major trends and patterns of change embedded in the overall process of economic, social and political transformation reshaping the urban challenges in eastern European cities. It reflects on important drivers of change such as efforts to create a market-based housing system and competitive housing markets in the post-communist urban world. The research draws much-needed attention to an important set of urban and housing policy issues with broad implications for understanding the transition process in the region. It explores the multi-layered processes of market-based housing reforms (privatisation, deregulation and devolution) and their impact on the spatial transformation of urban housing markets in eastern European cities. The main argument, supported with empirical evidence from a number of eastern European cities, is that the impact of these most significant processes of urban change has created a mosaic of diverse urban challenges. Exploring these urban challenges through the housing lens sets the stage for a better understanding of urban social movements in eastern European cities and their dynamic realities. The article argues that the diverse role of urban social movements can be explained by reference to democratic traditions, practices and policy cultures in eastern European cities, and also to institutional structures and the capacity of non-market stakeholders. In some cases, stronger government and governance traditions since the political changes of the 1990s would allow non-government organisations to "voice" their concerns and be accepted as a legitimate partner in coalitions responding to urban challenges. In other cases, such capacity and institutional collaboration may be non-existent, leading to "exit" and abandonment of formal systems. In the first option, urban social movements have resurrected debates about gentrification and social segregation in housing estates and neighbourhoods previously insulated from the market, fighting for their "rights to the city".In the latter option, individuals and organisations have resorted to informal solutions to growing housing inequalities, poverty and exclusion reflected in the massive growth of informal settlements and the illegality of urban construction.
Keywords: družbene spremembe; družene spremembe; mesta; politične spremembe; stanovanjska politika; stanovanjsko vprašanje; urbanism; urbanizem